Microemulsion electrolyte system and application thereof in lithium secondary battery
By constructing a fluorinated interface solvation layer in lithium secondary batteries using a microemulsion electrolyte system, the problem of synergistic optimization of the positive and negative electrode interfaces was solved, achieving high stability and safety of the battery, expanding the solvent selection space, and improving battery performance and lifespan.
Patent Information
- Application Number
- CN202510960237.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-11-14
AI Technical Summary
Existing technologies struggle to simultaneously optimize the positive and negative electrode interfaces in high-performance lithium secondary batteries, resulting in a lack of interfacial film components, which affects the battery's cycle stability and conductivity. Furthermore, high salt concentrations or high proportions of fluorinated solvents increase material costs and reduce battery performance.
An electrolyte system with a microemulsion structure is used to complex multiple locally fluorinated amphiphilic molecules with a perfluorinated organic solvent to form a stable interfacial solvation layer, thereby constructing a LiF-rich interfacial film and achieving simultaneous protection of the positive and negative electrodes.
It significantly improves the overall performance and compatibility of the electrolyte, extends battery cycle life, expands the solvent selection space, enhances battery safety and designability, and achieves high energy density and long life.
Smart Images

Figure CN120955219A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium secondary battery technology, specifically relating to a microemulsion electrolyte system and its application in lithium secondary batteries. Background Technology
[0002] In the development of high-performance lithium-ion rechargeable batteries, the design of the electrolyte system is one of the key aspects to achieving long-term stable operation. This is especially true in systems that simultaneously match a high-voltage positive electrode and a highly reducing negative electrode, where constructing a positive-to-negative electrode interphase (CEI / SEI) film with both chemical and electrochemical stability is crucial. Currently, the industry widely employs strategies such as adjusting the lithium salt to solvent ratio, reducing solvation capacity, or introducing functional anions to promote the participation of anions in the construction of the first solvation shell of lithium ions, thereby inducing the formation of anion-dominated solid electrolyte interphase film. These "solvation regulation" strategies, including high-concentration electrolytes, locally high-concentration electrolytes, perfluorinated solvent systems, and weakly solvated systems, have shown positive effects in improving the cycle stability of lithium metal anodes.
[0003] However, the above strategies still have significant limitations in the synergistic optimization of the positive and negative electrode interfaces. Because lithium ions migrate towards the negative electrode during charging driven by the electric field and concentration gradient, the vast majority of their paired anions also move to the negative electrode interface, resulting in a lack of composition at the positive electrode interface and making it difficult to simultaneously achieve stable CEI construction. Therefore, interface control strategies based on anion solvation behavior cannot simultaneously meet the requirements for positive and negative electrode interface regulation. Furthermore, such systems often rely on high salt concentrations or high proportions of fluorinated solvents, which not only significantly increases material costs but may also reduce the ionic conductivity of the electrolyte, affecting the battery's rate performance and energy efficiency. There is an urgent need to develop a novel interface regulation mechanism to achieve simultaneous protection of the positive and negative electrode interfaces. Summary of the Invention
[0004] To address the aforementioned issues, this invention proposes and implements a novel interface control method. By constructing a fluorinated interface solvation layer, it overcomes the bottleneck of existing technologies in the coordinated control of the two-electrode interface, significantly improving the overall performance and compatibility of the electrolyte, and has broad application prospects and promotional value.
[0005] In the microemulsion structure employed in this invention, micelles are formed by the complexation of multiple locally fluorinated amphiphilic molecules with a perfluorinated organic solvent, creating abundant liquid-liquid interfaces. These micelles can spontaneously accumulate on the electrode surface, forming a stable interfacial solvation layer. This solvation layer reduces the contact between highly reactive polar solvents and the electrode, effectively suppressing oxidation / reduction side reactions, extending battery cycle life, and improving electrochemical stability. Furthermore, this microemulsion electrolyte system overcomes the limitations of traditional electrolyte solvent selection, allowing novel solvents with specific functions but poor solubility to be effectively introduced into the electrolyte system through micelles and achieve functional release. This greatly expands the solvent selection space, improves the overall system's designability and functional compatibility, and provides synergistic protection for the electrolyte's high safety and long lifespan.
[0006] This invention discloses a microemulsion electrolyte for secondary batteries, comprising the following components: a polar electrolyte phase (BO), an insoluble solvent (AM), and a bridging solvent (IM), wherein the proportions of BO, AM, and IM solvents are 50-99 vol.%, 0.1-10 vol.%, and 0.1-50 vol.%, respectively.
[0007] The polar solvent in the polar electrolyte phase is selected from one or more of carbonates, ethers, carboxylic acid esters, nitriles and sulfones, as well as solvents that have undergone one or more fluorine substitutions.
[0008] The insoluble organic solvent is selected from one or more perfluorinated solvents;
[0009] The bridging solvent enables the polar solvent and the insoluble organic solvent to be miscible. The amphiphilic bridging solvent is a compound having at least one of the following: chain- or cyclic fluoroalkyl, chain- or cyclic fluoroalkenyl, chain- or cyclic fluoroalkynyl, or fluoroaryl, and one or more polar groups such as -COC-, -COO-, -CO-, -SO2-, -P=N-, -BO-, and -PO-.
[0010] Furthermore, the polar solvent is selected from one or more solvents such as carbonates, ethers, carboxylic esters, nitriles, and sulfones, capable of dissolving one or more lithium salts including lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium perchlorate, lithium bis(oxalate-borate), lithium nitrate, and lithium di(fluorooxalate-borate). The polar solvent is preferably selected from diethyl carbonate, fluoroethylene carbonate, and methyl ethyl carbonate.
[0011] Furthermore, the perfluorinated solvent does not dissolve electrolyte salts and has extremely low compatibility with polar electrolytes containing dissolved lithium salts. It is preferably one or more solvents selected from perfluoroalkanes, perfluorosilanes, perfluoroketones, perfluorosulfonyl fluorides, and perfluoroamines. The perfluorinated solvent is preferably one or more solvents selected from perfluorohexanoyl fluoride, perfluoropentanone, perfluorohexanone, pentadecyltriethylamine, perfluorohexane, perfluorobutane, perfluorooctane, perfluorodecane, perfluorononane, perfluorobutylsulfonyl fluoride, and perfluorohexylsulfonyl fluoride.
[0012] Furthermore, the amphiphilic bridging solvent is selected from bis(2,2,2-trifluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, hexafluorocyclotriphosphazene, pentafluoroethoxycyclotriphosphazene, pentafluorophenoxycyclotriphosphazene, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, tri(trifluoroethoxy)methyl One or more of the following: alkyl groups, bis(2,2,2-trifluoroethyl) ethers, tetrafluoro-1-(2,2,2-trifluoroethoxy)ethane, methoxyperfluorobutane, fluoromethylphenyl sulfone, methyl trifluoromethanesulfonate, tris(2,2,2-trifluoroethyl)boronic acid, 3-fluoro-2-butanone, N,N-dimethylaminosulfonyl fluoride, bis(2,2,2-trifluoroethyl) phosphate, and tris(2,2,2-trifluoroethyl) phosphate.
[0013] Furthermore, the additive is a sulfonate, a fluorinated ester, a siloxane, or a fluorosilane. Preferably, the additive is one or two of 3-fluoro-1,3-propanesulfonate lactone, trifluoroethyl acrylate, tetramethyltetravinylcyclotetrasiloxane, and vinyldimethylfluorosilane, with a mass fraction of 0.1%-5% of the microemulsion electrolyte. More preferably, the additive can polymerize into a film on the electrode surface to form a solid electrolyte phase, such as an inorganic-organic composite solid electrolyte phase.
[0014] Furthermore, the aforementioned electrolyte is optically transparent and exhibits significant Tyndall scattering under laser irradiation.
[0015] Furthermore, the electrochemical oxidation stability window of the electrolyte is >5.0V (vs. Li+ / Li), preferably >5.3V (vs. Li+ / Li), and more preferably >5.5V (vs. Li+ / Li), where (vs. Li+ / Li) indicates that the reference electrode is Li+ / Li.
[0016] Furthermore, the preparation method of the electrolyte:
[0017] S1: Mix the electrolyte salt and polar solvent in a certain proportion and stir to form a clear and transparent solution.
[0018] S2: When a certain proportion of perfluorinated organic compounds is added, phase separation occurs because the two phases are immiscible or have extremely low miscibility.
[0019] S3: Add some fluorinated amphiphilic compound, stir, and it becomes a clear and transparent solution again.
[0020] Furthermore, dynamic light scattering revealed the presence of particles ranging from 5 to 200 nm, with the size of the colloidal particles depending on the proportions of the solvent components.
[0021] S4: Add optional additives and stir until clear and transparent.
[0022] Furthermore, the electrolyte is characterized in that it is used as an electrolyte for lithium batteries, especially for lithium secondary batteries.
[0023] Furthermore, the added perfluorinated solvent can complex the fluorinated portions of multiple fluorinated amphiphilic solvents to form bridging solvent-encapsulated perfluorinated solvent nanoclusters, which are dispersed in the electrolyte as microscopic spherical structures of 5-200 nm. When used in battery systems, surface tension drives the fluorinated micelles to move from the electrolyte to the electrode-electrolyte interface, forming a stable F-rich interfacial solvation layer on the surface of the positive and negative electrode materials. The high-F solvent has high chemical and electrochemical stability, which can reduce the reaction between the electrolyte and the electrode, continuously stabilize the electrode-electrolyte interface, and improve the electrochemical performance of the battery under high voltage and high temperature.
[0024] This invention expands the range of solvents that can be used in electrolytes. Perfluorides, due to the extremely high bond energy of their CF bonds, exhibit excellent thermal stability, are generally non-flammable or extremely difficult to ignite, have high flash points, and do not release flammable gases at high temperatures, thus significantly improving the intrinsic safety of batteries. Simultaneously, perfluorides possess a very wide electrochemical stability window and exhibit fewer side reactions, making them a highly promising functional solvent choice for battery systems. However, perfluorides have extremely low polarity, resulting in significant incompatibility with commonly used polar solvents and lithium salts in conventional electrolytes. This makes it difficult for them to be uniformly dispersed and stably maintained in conventional electrolytes, thereby limiting their application in practical electrochemical systems.
[0025] To address this, this invention proposes a microemulsion electrolyte system. By using an amphiphilic bridging solvent with a fluoride-polarity affinity to regulate the formation of a stable micelle structure, perfluoride is effectively encapsulated within the fluorinated micelles, achieving uniform dispersion of the perfluoride on a macroscopic scale and structural stability on a microscopic scale. This strategy not only overcomes the limitation of poor solubility but also allows the perfluoride to participate in the construction of the interfacial stabilizing layer through interfacial structure regulation. This ensures electrolyte safety while maintaining excellent electrochemical performance, significantly enhancing the overall design freedom and application potential of the system. This design can form continuous protective layers with thicknesses of tens to hundreds of nanometers on the positive and negative electrode surfaces, achieving simultaneous stabilization and dual protection for both electrodes. The fluorinated phase introduced into the system has a dual-functional protection mechanism: firstly, the fluorinated solvent preferentially decomposes to generate a high-quality interfacial phase rich in LiF; secondly, the fluorinated micelles provide continuous dynamic interfacial coverage, effectively suppressing redox decomposition reactions of the electrolyte at the positive and negative electrode interfaces, thus improving the interfacial stability of the lithium secondary battery.
[0026] The beneficial effects of this invention include:
[0027] (1) The present invention provides a highly stable organic microemulsion electrolyte system that expands the selection space of solvents in electrolytes and introduces a second control dimension for electrolyte design, so that novel solvents with specific functions can be effectively introduced and utilized without relying on their solubility, thereby significantly improving the designability and compatibility of the system.
[0028] (2) The microemulsion electrolyte of the present invention effectively protects the positive and negative electrodes at the same time, while the fluorinated phase is enriched at the interface of the positive and negative electrodes to build a stable interface structure, which is conducive to inducing the formation of a solid electrolyte interface film (SEI / CEI) rich in LiF, and further enhancing the stability of the battery under harsh conditions such as high voltage or high temperature for long cycles.
[0029] (3) This invention proposes a design strategy for microemulsion electrolytes. The microemulsion electrolytes of this invention significantly improve the adaptability and controllability of electrolytes in high-performance lithium secondary batteries, and can be used to develop a new generation of energy storage devices with high energy density, high safety and long cycle life. Attached Figure Description
[0030] Figure 1 This is an optical photograph of the microemulsion electrolyte preparation process in Example 4 of the present invention.
[0031] Figure 2 This is a cryo-electron microscopy image of the microemulsion electrolyte in Example 4 of the present invention.
[0032] Figure 3 This is a cryo-electron microscopy image of the mixture of microemulsion electrolyte and positive electrode material NCM811 in Example 4 of the present invention.
[0033] Figure 4 The cycling performance of the microemulsion electrolyte in Example 4 of this invention and the electrolytes in Comparative Examples 1 and 2 in a Li||NCM811 battery was measured in the voltage range of 3.0-4.5V and the test temperature was 50℃.
[0034] Figure 5 The results of the needle penetration test of the microemulsion electrolyte in Example 1 of this invention under full charge (4.5V) after 30 cycles of a 7Ah soft-pack battery. Detailed Implementation
[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0036] Examples 1-8: 1M lithium difluorooxalate borate (LiDFOB) and 0.2M lithium tetrafluoroborate (LiBF4) were dissolved in diethyl carbonate (DEC)-fluoroethylene carbonate (FEC) (2:1, v / v) polar solvent as the first phase. 1 ml of the above electrolyte was taken, and 5% by volume of a perfluorinated compound was added as the insoluble phase. It can be seen that the insoluble phase droplets settled at the bottom of the electrolyte. While stirring, the bridging phase 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether was added dropwise as a bridging solvent until the two phases were just miscible. The polarity of the perfluorinated compound affected the amount of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether added.
[0037] Comparative Example 1 used only 1 mL of 1M LiDFOB-0.2M LiBF4 in FEC / DEC, while Comparative Example 2 used 1 mL of 1M LiDFOB-0.2M LiBF4 in FEC / DEC and 270 μL of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0038] Table 1: Components and proportions of Examples 1-8 and Comparative Examples 1-2
[0039]
[0040] Li||LiNi was assembled using an electrolyte in an argon-filled glove box. 0.8 Co 0.1 Mn 0.1O2(NCM811)CR2032 button half-cells were used with polypropylene as the separator. The compatibility of this organic microemulsion electrolyte with high-voltage Li||NCM811 was tested. A soft-pack battery of Li||NCM811 was assembled and its safety performance was tested.
[0041] A three-electrode system was used to test the electrochemical stability window of the electrolyte, with a Pt electrode as the working electrode, to investigate the oxidative stability of the electrolyte (current reaching 0.01 mA cm⁻¹). -2 The corresponding voltage is the electrochemical oxidation stability window.
[0042] Table 2: Capacity retention and safety performance characterization of Li||NCM811 batteries under high voltage cycling in Examples 1-8 and Comparative Examples 1-2.
[0043]
[0044]
[0045] Therefore, in Examples 1-8 and Comparative Examples 1-2, the polar solvents were the same, and there was no insoluble phase. Comparative Examples 1-2, with or without the addition of a bridging phase, all experienced ignition and even explosions, failing to meet the usage requirements. Among Examples 1-8 with the addition of an insoluble phase, Example 4 performed best, using perfluorohexylsulfonyl fluoride, followed by Example 1, using perfluorohexanone. Other perfluorinated compounds, including perfluoroheptane, perfluorobutylsulfonyl fluoride, pentadecyltriethylamine, perfluorohexanoyl fluoride, perfluorohexane, and perfluorooctane, also performed adequately to meet the usage requirements. This indicates that the organic microemulsion electrolyte has good compatibility with high-voltage positive electrodes and highly reduced lithium metal negative electrodes, effectively suppressing gas generation and positive electrode structure degradation under high voltage.
[0046] Furthermore, in the electrochemical oxidation stability window (vs. Li+ / Li), all examples showed an effect of 5.0V, or even 5.4V, with Examples 1 and 4 reaching above 5.50V. (vs. Li+ / Li) indicates that the reference electrode is Li+ / Li.
[0047] It is possible that perfluorohexylsulfonyl fluoride, due to its lower LUMO and higher HOMO energy levels, is more likely to participate in electron transfer processes at the electrode interface, preferentially forming a LiF-rich interfacial phase, which contributes to improved interfacial stability. Simultaneously, the presence of S=O and C=O groups can reduce the content of the bridging phase while maintaining micellar structure stability, resulting in smaller micellar particles. This significantly mitigates the adverse effects of fluorinated phase introduction on conductivity under the same conditions, achieving synergistic optimization of stability and ion transport performance.
[0048] Examples 9-22: 1M LiDFOB-0.2M LiBF4 was dissolved in ethyl methyl carbonate (EMC)-fluoroethylene carbonate (2:1, v / v) polar solvent as the first phase. 1 ml of the above electrolyte was taken and 3% by volume of perfluorohexyl sulfonyl fluoride was added. A clear phase separation could be seen. Different bridging solvents were added dropwise to the system while stirring until the two phases were just miscible.
[0049] Table 3: Components and proportions of Examples 9-22 and Comparative Examples 3-5
[0050]
[0051]
[0052] Table 4. Capacity retention of Li||NCM811 batteries in the electrolytes of Examples 9-22 and Comparative Examples 3-5 under normal temperature high voltage and high temperature high voltage cycling.
[0053]
[0054]
[0055] Therefore, in Examples 9-22 and Comparative Examples 3-5, the retention rate after cycling was lower in Comparative Examples 3-5 without the addition of an insoluble phase. After adding an insoluble phase, among the different bridging phases, tris(2,2,2-trifluoroethyl)borate in Example 22 was the most effective. Among other bridging solvents, hexafluorocyclotriphosphazene and tris(2,2,2-trifluoroethyl) phosphate were also relatively effective. In addition, pentafluoroethoxycyclotriphosphazene was relatively less effective than tris(2,2,2-trifluoroethyl)borate, hexafluorocyclotriphosphazene, and tris(2,2,2-trifluoroethyl) phosphate.
[0056] Without the formation of a microemulsion structure, introducing a bridging phase alone is often insufficient to achieve structural uniformity and interfacial stability, resulting in limited performance improvement. In this invention, the bridging phase is preferably a fluorinated phosphate ester or a borate ester compound. These compounds possess relatively low HOMO energy levels and exhibit certain antioxidant stability. During the electrochemical reaction, their decomposition products contain elements such as P / B and F, which can induce the formation of a multi-element-rich interfacial film structure at the electrode interface, thereby improving interfacial stability to a certain extent and enhancing the battery's cycle performance under high pressure and high temperature conditions.
[0057] Bridging phase molecules such as methyl trifluoromethanesulfonate, N,N-dimethylaminosulfonyl fluoride, and 3-fluoro-2-butanone contain relatively reactive functional groups (such as sulfonates, aminosulfonyl groups, and ketone carbonyl groups) in their intrinsic molecular structures. They also have relatively low molecular weights, high volatility, and relatively low boiling points (typically below 170°C), making them prone to decomposition or side reactions under high temperature or high voltage conditions. Furthermore, these molecules exhibit relatively poor oxidative stability, with electron cloud density concentrated in highly electronegative groups (such as –SO3CF3, –SO2NF2, –CO–), leading to easy oxidation under high voltage conditions. Therefore, under high temperature and high voltage conditions of 4.5–4.7V, the thermal and electrochemical stability of these bridging phases is insufficient, making it difficult to maintain the integrity and functionality of the interfacial film, resulting in a slightly lower capacity retention rate of the assembled battery during long-term cycling.
[0058] Furthermore, this invention can specifically introduce additives into the microemulsion electrolyte. These additives are sulfonates, fluorinated esters, siloxanes, or fluorosilanes. These additives can undergo electrochemical in-situ polymerization on the electrode surface. The polymerization products synergistically participate in the construction of the SEI / CEI film with the decomposition components of the fluorinated phase. Siloxane additives form a unique organic-inorganic hybrid structure. The silicon-oxygen network (Si-O-Si) generated by silanes provides skeletal support (increasing the elastic modulus by 2-3 times), while LiF nanocrystals are uniformly distributed in the organic matrix. This composite interface film not only exhibits excellent lithium-ion conductivity (Li+ transport number > 0.65), but the introduction of silicon significantly improves the high-temperature stability of the electrolyte, enabling the battery to exhibit excellent cycle performance over a wide temperature range (-20 to 60°C). Similarly, fluorosilanes can also provide the above support, and with even better results.
[0059] Examples 23-25: 1M LiDFOB-0.2M LiBF4 was dissolved in a polar solvent of ethyl methyl carbonate (EMC)-fluoroethylene carbonate (2:1, v / v) as the first phase. 1 ml of the above electrolyte was taken, and 3% (v / v) of perfluorohexyl sulfonyl fluoride was added as the insoluble phase. Tris(2,2,2-trifluoroethyl) borate was added dropwise to this system while stirring until the two phases were just miscible. 1% (w / w) of 3-fluoro-1,3-propanesulfonate lactone, tetramethyltetravinylcyclotetrasiloxane, or vinyldimethylfluorosilane was added to the above electrolyte.
[0060] Table 5: Components of Examples 22-25
[0061]
[0062] Table 6: Capacity retention and high-temperature storage performance of Li||NCM811 batteries in the electrolytes of Examples 22-25 under cycling at room temperature (25°C) and high temperature (50°C) and high voltage.
[0063]
[0064]
[0065] The above indicates that adding 3-fluoro-1,3-propanesulfonate lactone, tetramethyltetravinylcyclotetrasiloxane, or vinyldimethylfluorosilane to the system can improve electrochemical performance, such as capacity retention and capacity recovery, with silanes and fluorosilanes showing better effects.
[0066] Table 7: Components and proportions in the electrolytes of Examples 22, 26, and 27
[0067]
[0068] In Example 26, due to the low content of the bridging phase, the 3% insoluble phase could not be completely dissolved. Therefore, the supernatant was used to assemble the battery. In Examples 27 and 22, the electrolytes were clear and transparent.
[0069] Table 8: High voltage retention rate of Li||NCM811 battery at room temperature in electrolytes of Examples 22, 26, and 27
[0070]
[0071] The above shows that when the bridging phase does not completely mix the polar phase and the insoluble phase (Example 26), the electrolyte effect is slightly inferior. The effect is best when the appropriate amount of bridging phase is sufficient to completely mix the polar phase and the insoluble phase (Example 22). A slight excess of bridging phase (Example 27) will lead to a slight decrease in performance.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the embodiments of the present invention, and are not intended to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the protection scope of the present invention.
Claims
1. A microemulsion electrolyte for secondary batteries, characterized in that: It comprises the following components: a polar electrolyte phase (BO), an insoluble solvent (AM), and a bridging solvent (IM), wherein the volume ratio of each of the BO, AM, and IM solvents is 100:(0.1-10):(0.1-50); and also includes optional additives; The polar solvent in the polar electrolyte phase is selected from one or more of carbonates, ethers, carboxylic acid esters, nitriles and sulfones, as well as solvents that have undergone one or more fluorine substitutions. The insoluble organic solvent is selected from one or more perfluorinated solvents; The bridging solvent enables the polar solvent and the insoluble organic solvent to be miscible. The amphiphilic bridging solvent is a compound having at least one of the following: chain- or cyclic fluoroalkyl, chain- or cyclic fluoroalkenyl, chain- or cyclic fluoroalkynyl, or fluoroaryl, and one or more -COC-, -COO-, -CO-, -SO2-, -P=N-, -BO-, and -PO- as polar groups.
2. The microemulsion electrolyte according to claim 1, characterized in that, The polar solvent is selected from one or more of carbonates, ethers, carboxylic acid esters, nitriles and sulfones, as well as solvents that have undergone one or more fluorine substitutions. The polar solvent is capable of dissolving one or more lithium salts selected from lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium perchlorate, lithium bis(oxalate-borate), lithium nitrate, and lithium di(fluorooxalate-borate). The polar solvent is preferably selected from one or more of diethyl carbonate, fluoroethylene carbonate, and methyl ethyl carbonate.
3. The microemulsion electrolyte according to claim 1, characterized in that, The perfluorinated solvent does not dissolve electrolyte salts and has extremely low compatibility with polar electrolytes containing dissolved lithium salts. The perfluorinated solvent is preferably one or more solvents selected from perfluoroalkanes, perfluorosilanes, perfluoroketones, perfluorosulfonyl fluorides, and perfluoroamines; more preferably one or more solvents selected from perfluorohexanoyl fluoride, perfluoropentanone, perfluorohexanone, pentadecyltriethylamine, perfluorohexane, perfluorobutane, perfluorooctane, perfluorodecane, perfluorononane, perfluorobutylsulfonyl fluoride, and perfluorohexylsulfonyl fluoride.
4. The microemulsion electrolyte according to claim 1, characterized in that, The amphiphilic bridging solvent is selected from bis(2,2,2-trifluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, hexafluorocyclotriphosphazene, pentafluoroethoxycyclotriphosphazene, pentafluorophenoxycyclotriphosphazene, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, tris(trifluoroethoxy)methane, bis... One or more of the following: (2,2,2-trifluoroethyl) ether, tetrafluoro-1-(2,2,2-trifluoroethoxy) ethane, methoxyperfluorobutane fluoromethylphenyl sulfone, methyl trifluoromethanesulfonate, tris(2,2,2-trifluoroethyl)boronic acid, 3-fluoro-2-butanone, N,N-dimethylaminosulfonyl fluoride, bis(2,2,2-trifluoroethyl) phosphate, and tris(2,2,2-trifluoroethyl) phosphate.
5. The electrolyte according to claim 1, characterized in that, The additive is a sulfonate, a fluorinated ester, a siloxane, or a fluorosilane. Preferably, the additive is one or two of 3-fluoro-1,3-propanesulfonate lactone, trifluoroethyl acrylate, tetramethyltetravinylcyclotetrasiloxane, and vinyldimethylfluorosilane. Preferably, the mass fraction of the additive is 0.1%-5% of the microemulsion electrolyte. More preferably, the additive can polymerize into a film on the electrode surface to form a solid electrolyte phase, such as an inorganic-organic composite solid electrolyte phase. Further preferably, the additive is one or two of tetramethyltetravinylcyclotetrasiloxane and vinyldimethylfluorosilane.
6. The electrolyte according to any one of claims 1-5, characterized in that, It is optically transparent and preferably exhibits significant Tyndall scattering under laser irradiation.
7. The electrolyte according to any one of claims 1-6, characterized in that: The electrolyte has an electrochemical oxidation stability window > 5.0V (vs. Li+ / Li), preferably > 5.3V (vs. Li+ / Li), and more preferably > 5.5V (vs. Li+ / Li), where (vs. Li+ / Li) indicates that the reference electrode is Li+ / Li.
8. The electrolyte according to any one of claims 1-7, comprising a polar electrolyte phase (BO), an insoluble solvent (AM), and a bridging solvent (IM), wherein the ratio of BO, AM, and IM solvents to additives is 100:(0.1-10):(0.1-50):(0.1-5).
9. A method for preparing the electrolyte according to any one of claims 1-8: characterized in that: S1: Mix the electrolyte salt and polar solvent in a certain proportion and stir to form a clear and transparent solution; S2: When a certain proportion of perfluorinated organic compounds is added, phase separation occurs because the two phases are immiscible or have extremely low miscibility. S3: Add some fluorinated amphiphilic compound, stir and it becomes a clear and transparent solution again. Further, dynamic light scattering shows the presence of 5-200nm particles. The size of the colloidal particles depends on the proportion of each solvent component. S4: Add optional additives and stir until clear and transparent.
10. The use of the electrolyte according to any one of claims 1-8, characterized in that: Used in lithium battery electrolytes, especially lithium secondary battery electrolytes.
Citation Information
Cited By
Supercritical lithium metal battery electrolyte with electric field adaptability and application
CN121546168A